Volume-dependent response of precooling for intermittent-sprint exercise in the heat - Minett, G. M.; Duffield, R.; Marino, F. E.; Portus, M. (Medicine & Science in Sports & Exercise, 2011)
Purpose: This study aimed to assess the effects of precooling volume on neuromuscular function and performance in free-paced intermittent-sprint exercise in the heat.